Facile synthesis of stable colloidal suspension of amorphous carbon nanoparticles in aqueous medium and their characterization. (September 2018) - Tegafaw, Tirusew; Oh, In Taek; Cha, Hyunsil; Yue, Huan; Miao, Xu; Ho, Son Long; Ahmad, Mohammad Yaseen; Marasini, Shanti; Ghazanfari, Adibehalsadat; Kim, Hee-Kyung; Chae, Kwon Seok; Chang, Yongmin; et al.
Abstract: In this study, amorphous carbon nanoparticles (CNPs) with an average diameter of 2.2 nm were synthesized by reducing dextrose (C6 H12 O6 ) with sodium hydroxide in an aqueous medium. The amorphous CNPs formed stable colloidal suspensions in water owing to the presence of hydrophilic functional groups on the nanoparticle surfaces. The amorphous CNPs exhibited ultraviolet (UV)-visible absorption (λabs ) at 267 nm and emission (λem ) at 453 nm under UV irradiation; thus, the colloidal suspension appeared sky-blue in color under UV irradiation. The amorphous CNPs were paramagnetic with weak magnetization at room temperature and exhibited small longitudinal (r1 ) and transverse (r2 ) water proton relaxivities of 0.036 and 0.068 s −1 mM −1, respectively. The amorphous CNPs exhibited no cellular toxicity up to the measured carbon concentration of 500 μM and presented fluorescence microscopy images on a micrometer scale, thus demonstrating their utility in fluorescence bio-imaging applications. Graphical abstract: Highlights: The amorphous CNPs with an average diameter of 2.2 nm were synthesized in an aqueous medium. The CNPs were non-toxic and formed stable colloidal suspensions in water. The CNPs were paramagnetic and exhibited weak magnetization at room temperature. The CNPs exhibited small water proton relaxivities. Fluorescence microscopy demonstrated the utility of the CNPs in fluorescence bio-imaging applications.